Levels of Mobility in Children and Adolescents with Spina Bifida—Clinical Parameters Predicting Mobility and Maintenance of These Skills - Pauly, Marcus; Cremer, Reinhold (European Journal of Pediatric Surgery, 2013)
Purpose The retrospective study was performed to apply the “Hoffer criteria” as a suitable classification of mobility in spina bifida patients. We looked at clinical parameters and factors that can be used as predictors for future mobility and development in these patients.Materials and Methods Clinical data about ambulation of 90 spina bifida/myelomeningocele patients were collected using a questionnaire and were completed using the medical records of the patients. The patients were grouped by their walking distances according to “Hoffeŕs criteria” (community walker, household walker, exercise walker, nonwalker). The development of the mobility skills over the years was documented.Results We grouped 42% of the patients as community walkers, 16% as household, 16% as exercise walkers, and 27% as always wheelchair dependent (nonwalker). We found significant correlations between the Hoffer criteria, the level of lesion the walking distance and the ability to stand upright. There is also a significant relation between the Hoffer criteria and the frequency of fractures and the age of the patients. The occurrence of fractures is directly related to the level of lesion and to the level of mobility in our group of patients. Of all our patients, 39% patients had improved in mobility, 37% patients retained their achieved state, and 24% worsened in their mobility skills.Conclusions We could see that a stable and ambitious milieu and care in specialized institutions can achieve a high level of ambulation in spina bifida patients. Most patients are able to maintain this skill over a long period of time. Predictive factors to maintain mobility in patients with myelomeningoceles (spina bifida) are not only dependent on the level of lesion but also rely on the aftercare of the patients too. The data that were collected are used for counseling of parents and patients.
Keywords: mobility; spina bifida; ambulation